Peripheral neuropathy associated with tofacitinib use in alopecia universalis - Raghad Alharthi; Fatimah Alowirdi; Saba Alsuhaymi; Mohammed AlQahtani; Afaf Alsheikh (Wolters Kluwer Medknow Publications, 2022)
Alopecia areata (AA) is an autoimmune disease characterized by nonscarring hair loss. Alopecia universalis (AU) is the advanced form of AA characterized by complete scalp and body hair loss. Traditional medical therapies for AA include topical and intralesional corticosteroids, topical anthralin immunotherapy, and light therapy. Tofacitinib is a Janus kinase-1 and 3 inhibitor used in the treatment of AA. In this report, we describe a 20-year-old female with AU refractory to topical therapies; thus, she was started on tofacitinib. Mild peripheral neuropathy was an unanticipated side effect that could be kept into consideration.